"Punitive reformation": state-sanctioned labour through criminal justice and welfare - Jon Burnett (Revisiting Crimes of the Powerful: Marxism, Crime and Deviance, 2018)
This chapter examines an aspect of the “imaginary social order” that was integral to the analysis within Crimes of the Powerful, but has rarely been adequately explored: the “belief that the interests of labour are essentially the same as the interests of capital”. As Frank Pearce powerfully demonstrated, considerable ideological work went into constructing and reproducing the idea that the relationship between labour and capital was basically consensual, and certainly democratic, in the forms of social order that were the subject of his analysis. Yet despite the importance of this insight – not least for its contribution to the theorisation of the state within Crimes of the Powerful – it is an observation that some four decades later needs expansion. Against the backdrop of the sustained neoliberal revolution that has swept through the political and cultural landscape, unwaged or-sub-waged labour has been (re)embedded and reformulated in the delivery of mainstream welfare and criminal policy